Orphanage trafficking in international law / Kathryn E. van Doore. - Van Doore, Kathryn E., 1980- (Cambridge University Press, 2022)
Orphanage Trafficking in International Law explores the process of orphanage trafficking as a form of child trafficking in international law, examining the contexts in which it occurs and providing a comprehensive, holistic approach to addressing the issue as a form of trafficking. In doing so, this book establishes the method and process of orphanage trafficking as an issue of international concern. It reconceptualises the activity of orphanage tourism as a demand driver for child trafficking and a form of exploitation, and makes recommendations for how countries where orphanage trafficking occurs, as well as countries that contribute to orphanage trafficking via funding and volunteers, should tackle the issue.